2006
DOI: 10.1126/science.1126308
|View full text |Cite
|
Sign up to set email alerts
|

Bruchpilot Promotes Active Zone Assembly, Ca 2+ Channel Clustering, and Vesicle Release

Abstract: The molecular organization of presynaptic active zones during calcium influx-triggered neurotransmitter release is the focus of intense investigation. The Drosophila coiled-coil domain protein Bruchpilot (BRP) was observed in donut-shaped structures centered at active zones of neuromuscular synapses by using subdiffraction resolution STED (stimulated emission depletion) fluorescence microscopy. At brp mutant active zones, electron-dense projections (T-bars) were entirely lost, Ca2+ channels were reduced in den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

43
814
6
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 748 publications
(868 citation statements)
references
References 39 publications
43
814
6
5
Order By: Relevance
“…To test this, we quantified Nlg1 intensity (as a measure of Nlg1 clustering) in mutants for presynaptic brp (brp 1.3 ) 20 . The brp mutant larvae show a stronger decrease in presynaptic neurotransmitter release than any of the mutants discussed above 5,11,20,22,23 . Nlg1 clusters, however, were not reduced in brp mutants (Fig.…”
Section: Lam Gmentioning
confidence: 80%
See 2 more Smart Citations
“…To test this, we quantified Nlg1 intensity (as a measure of Nlg1 clustering) in mutants for presynaptic brp (brp 1.3 ) 20 . The brp mutant larvae show a stronger decrease in presynaptic neurotransmitter release than any of the mutants discussed above 5,11,20,22,23 . Nlg1 clusters, however, were not reduced in brp mutants (Fig.…”
Section: Lam Gmentioning
confidence: 80%
“…Nlg1 clusters, however, were not reduced in brp mutants (Fig. 3c,d), indicating that the observed reduction of Nlg1 in Syd-1 and Nrx-1 mutants was neither due to reduced transmission nor a reflection of a general active zone assembly deficit (which is very pronounced in brp mutants 22 ). Instead, Syd-1 seems to be specifically involved in clustering postsynaptic Nlg1 adjacent to synapses.…”
Section: Lam Gmentioning
confidence: 87%
See 1 more Smart Citation
“…The importance of the CAZ in orchestrating neurotransmitter release is further exemplified by the fact that flies with null alleles of BRP 29 show loss of the electron-dense active zone cytomatrix, a morphological defect that is correlated with impaired clustering of voltage-gated Ca 2+ channels and with desynchronization of glutamate release. Alterations in activity-dependent synaptic vesicle exocytosis are also seen upon knockdown of the giant CAZ protein piccolo 30 .…”
Section: Box 1 | Presynaptic Organization -Exocytic and Endocytic Zonesmentioning
confidence: 99%
“…Genetic analysis of presynaptic scaffolds has also turned out to be difficult because of the complex (broad) phenotypes resulting from null alleles. For example, deletion of the active zone component BRP in Drosophila melanogaster causes a severe loss of active zone dense bodies (T-bars) and a concomitant declustering of presynaptic Ca 2+ channels, provoking a severe deficit in baseline synaptic vesicle release 29 . A recent study 107 identified a hypomorphic allele termed brp nude , lacking merely the last 17 amino acids (that is, <1% of all residues) of BRP.…”
Section: Calcium Regulationmentioning
confidence: 99%